2023
DOI: 10.1002/jat.4437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasticizer diisobutyl adipate on the Japanese medaka (Oryzias latipes) endocrine system

Abstract: Plasticizer pollution of the water environment is one of the world's most serious environmental issues. Phthalate plasticizers can disrupt endocrine function in vertebrates. Therefore, this study analyzed thyroid‐related, reproduction‐related, and estrogen‐responsive genes in Japanese medaka (Oryzias latipes) to determine whether non‐phthalate diisobutyl adipate (DIBA) plasticizer could affect endocrine hormone activity or not. Developmental toxicity during fish embryogenesis was also evaluated. At a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…89 First, evidence indicated that DIBA (a similar compound to DBA) is embryotoxic and disrupts thyroid hormone activity in fish. 90 The study stated that embryonic exposure to DIBA at 11.57 mg L −1 increased the mortality rate. Furthermore, abnormal development, growth inhibition, and reduced swimming performance were observed at 3.54 and 11.57 mg L −1 concentrations of DIBA.…”
Section: Emerging or Alternative Plasticizersmentioning
confidence: 98%
See 2 more Smart Citations
“…89 First, evidence indicated that DIBA (a similar compound to DBA) is embryotoxic and disrupts thyroid hormone activity in fish. 90 The study stated that embryonic exposure to DIBA at 11.57 mg L −1 increased the mortality rate. Furthermore, abnormal development, growth inhibition, and reduced swimming performance were observed at 3.54 and 11.57 mg L −1 concentrations of DIBA.…”
Section: Emerging or Alternative Plasticizersmentioning
confidence: 98%
“…Additionally, DIBA exposure altered thyroid hormone-related markers, increasing tshβ and dio1 levels while decreasing trα and trβ levels. 90 A recent study conducted by Horie et al (2024) 91 assessed the endocrine-disrupting effects of DIBA. This involved analyzing the expression levels of genes responsive to endocrine dis-Fig.…”
Section: Emerging or Alternative Plasticizersmentioning
confidence: 99%
See 1 more Smart Citation